A proposed reverse transcription mechanism for (CAG)n and similar expandable repeats that cause neurological and other diseases - Andrew Franklin; Edward J. Steele; Robyn A. Lindley (Heliyon, 2020)
The mechanism of (CAG)n repeat generation, and related expandable repeat diseases in non-dividing cells, is currently understood in terms of a DNA template-based DNA repair synthesis process involving hairpin stabilized slippage, local error-prone repair via MutSβ (MSH2–MSH3) hairpin protective stabilization, then nascent strand extension by DNA polymerases-β and -δ. We advance a very similar slipped hairpin-stabilized model involving MSH2–MSH3 with two key differences: the copying template may also be the nascent pre-mRNA with the repair pathway being mediated by the Y-family error-prone enzymes DNA polymerase-η and DNA polymerase-κ acting as reverse transcriptases. We argue that both DNA-based and RNA-based mechanisms could well be activated in affected non-dividing brain cells in vivo. Here, we compare the advantages of the RNA/RT-based model proposed by us as an adjunct to previously proposed models. In brief, our model depends upon dysregulated innate and adaptive immunity cascades involving AID/APOBEC and ADAR deaminases that are known to be involved in normal locus-specific immunoglobulin somatic hypermutation, cancer progression and somatic mutations at many off-target non-immunoglobulin sites across the genome: we explain how these processes could also play an active role in repeat expansion diseases at RNA polymerase II-transcribed genes.